Ammonium Ion Batteries: Material, Electrochemistry and Strategy - Zheng, Runtian; Li, Yuhang; Yu, Haoxiang; Zhang, Xikun; Yang, Ding; Yan, Lei; Li, Yu; Shu, Jie; Su, Bao‐Lian (Angewandte Chemie International Edition, 2023)
Ammonium‐ion batteries (AIBs) have recently attracted increasing attention in the field of aqueous batteries owing to their high safety and fast diffusion kinetics. The NH4+ storage mechanism is quite different from that of spherical metal ions (e.g. Li+, Na+, K+, Mg2+, and Zn2+) because of the formation of hydrogen bonds between NH4+ and host materials. Although many materials have been proposed as electrode materials for AIBs, their performances hardly meet the requirement of future electrochemical energy storage devices. It is thus urgent to design and exploit advanced materials for AIBs. This review highlights the state‐of‐the‐art research on AIBs. The insights into the basic configuration, operating mechanism and recent progress of electrode materials and corresponding electrolytes for AIBs have been comprehensively outlined. The electrode materials are classified and compared according to different NH4+ storage behaviour in the structure. The challenges, design strategies and perspectives are also discussed for the future development of AIBs. Ammonium‐ion batteries have shown great potential due to their unique advantages including their high safety and fast diffusion kinetics in low‐cost energy storage systems. Compared with the common metal cations batteries AIBs offer great advantages of favorable sustainability and fast diffusion kinetics through hydrogen bonding in different electrode materials.